Theoretical considerations about small mammals abundance on an epidemiological context (2017)
"To have a good trapping design before conducting scientific experiments on the field is important because this will allow generating accurate planning policies to accomplish specific researcher criteria. In particular, studies that involve small mammals analysis represent a challenge since the individuals are not directly observable. We proposed a methodology that aims to generate optimal designs for the criteria of capturing a higher number of individuals. The proposed scheme consist of two components (1) The population home range centers for a study region B are obtained as a realization of A non-homogeneous Poisson Space Point process whose intensity parameters are fitted using observations from a region A. (2) To apply an optimization criteria to seek the optimal live traps configuration for an information- objective function over the B region." -- Tomado del Formato de Documento de Grado.